Methylsulfonylmethane (MSM) as a New Target for the Treatment of Glycerol-Induced Nephropathy - Shaza Anwar Al Laham (Journal of Pharmacy and Nutrition Sciences, 2018)
Objective: Methylsulfonylmethane (MSM) is a naturally occurring nutrient composed of sulfur, oxygen and methyl groups. MSM may have anti-inflammatory and free radical scavenging activity. The present work was done to investigate the possible cure effect of methylsulfonylmethane on glycerol-induced acute renal failure (ARF) in rats. Methodes: After water deprivation, a kidney injury was induced in rats by intramuscular administration of glycerol 10 mL/kg (50% vol./vol. in saline). Several parameters including macroscopic score, histopathological and biochemical were determined to assess the degree of treatment. Results: Results showed that MSM decreased macroscopic and microscopic kidney’s injury scores caused by glycerol. MSM also significantly reduced urea and creatinine levels compared to glycerol-induced ARF group. Conclusion: MSM as a natural product has a curing effect against glycerol-induced myoglobinuria.